Genetic and epigenetic alterations in normal and sensitive COPD-diseased human bronchial epithelial cells repeatedly exposed to air pollution-derived PM2.5. (November 2017) - Leclercq, B.; Platel, A.; Antherieu, S.; Alleman, L.Y.; Hardy, E.M.; Perdrix, E.; Grova, N.; Riffault, V.; Appenzeller, B.M.; Happillon, M.; Nesslany, F.; Coddeville, P.; et al.
Abstract: Even though clinical, epidemiological and toxicological studies have progressively provided a better knowledge of the underlying mechanisms by which air pollution-derived particulate matter (PM) exerts its harmful health effects, further in vitro studies on relevant cell systems are still needed. Hence, aiming of getting closer to the human in vivo conditions, primary human bronchial epithelial cells derived from normal subjects (NHBE) or sensitive chronic obstructive pulmonary disease (COPD)-diseased patients (DHBE) were differentiated at the air-liquid interface. Thereafter, they were repeatedly exposed to air pollution-derived PM2.5 to study the occurrence of some relevant genetic and/or epigenetic endpoints. Concentration-, exposure- and season-dependent increases of OH-B[ a ]P metabolites in NHBE, and to a lesser extent, COPD-DHBE cells were reported; however, there were more tetra-OH-B[ a ]P and 8-OHdG DNA adducts in COPD-DHBE cells. No increase in primary DNA strand break nor chromosomal aberration was observed in repeatedly exposed cells. Telomere length and telomerase activity were modified in a concentration- and exposure-dependent manner in NHBE and particularly COPD-DHBE cells. There were a global DNA hypomethylation, a P16 gene promoter hypermethylation, and a decreasing DNA methyltransferase activity in NHBE and notably COPD-DHBE cells repeatedly exposed. Changes in site-specific methylation, acetylation, and phosphorylation of histone H3 (i.e., H3K4me3, H3K9ac, H3K27ac, and H3S10ph) and related enzyme activities occurred in a concentration- and exposure-dependent manner in all the repeatedly exposed cells. Collectively, these results highlighted the key role played by genetic and even epigenetic events in NHBE and particularly sensitive COPD-DHBE cells repeatedly exposed to air pollution-derived PM2.5 and their different responsiveness. While these specific epigenetic changes have been already described in COPD and even lung cancer phenotypes, our findings supported that, together with genetic events, these epigenetic events could dramatically contribute to the shift from healthy to diseased phenotypes following repeated exposure to relatively low doses of air pollution-derived PM2.5 . Graphical abstract: Highlights: Innovative in vitro exposure systems to be closer to the human in vivo conditions. Experimental strategy of repeated exposure to air pollution-derived PM2.5 samples. Better knowledge on the interaction between the genetic and epigenetic endpoints. Highest responsiveness of COPD-DHBE cells to air pollution-derived PM2.5 . Shift from healthy to COPD phenotypes by the exposure to air pollution-derived PM2.5 . Abstract : Together with genetic events, epigenetic alterations could dramatically contribute to the shift from healthy to diseased phenotypes following repeated exposure to relatively low doses of air pollution-derived PM2.5 .